2013
DOI: 10.1080/08927022.2013.811722
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of separation of C2H6from CH4using zeolitic imidazolate frameworks

Abstract: Separation of important chemical feedstocks, such as C 2 H 6 from natural gas, can greatly benefit the petrochemical industry. In this paper, the grand canonical Monte Carlo method has been used to study the adsorption and separation of CH 4 and C 2 H 6 in zeolites, isoreticular metal-organic framework-1 (IRMOF-1) and zeolitic imidazolate frameworks (ZIFs) with different topology, including soadlite, gmelinite and RHO topologies. Compared with mordenite zeolite and IRMOF-1, ZIFs and mordenite framework inverte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…Theoretical simulation is a powerful tool enabling us to unveil the adsorption mechanisms and providing us the information on adsorption sites. Hence, GCMC simulations were performed for understanding the interactions and adsorption behaviors of C 3 H 6 in iso-MOF-4 at the molecular level. ,, The density distributions of C 3 H 6 and C 2 H 4 molecules mass center within the structure at 298 K under different pressures were analyzed (Figure a–f). As expected, the potential adsorption sites are located around the paddlewheel secondary building units (SBUs).…”
Section: Resultsmentioning
confidence: 99%
“…Theoretical simulation is a powerful tool enabling us to unveil the adsorption mechanisms and providing us the information on adsorption sites. Hence, GCMC simulations were performed for understanding the interactions and adsorption behaviors of C 3 H 6 in iso-MOF-4 at the molecular level. ,, The density distributions of C 3 H 6 and C 2 H 4 molecules mass center within the structure at 298 K under different pressures were analyzed (Figure a–f). As expected, the potential adsorption sites are located around the paddlewheel secondary building units (SBUs).…”
Section: Resultsmentioning
confidence: 99%
“…The bulk gas composition of both mixtures was assumed to be equimolar in all molecular simulations because Guo et al (Guo et al, 2014) recently showed that composition does not strongly affect C 2 H 6 selectivity of a MOF material.…”
Section: Predicting Separation Performances Of Mofsmentioning
confidence: 99%
“…Bux et al (Bux et al, 2011) used GCMC simulations to estimate single-component adsorption of C 2 H 6 and C 2 H 4 in ZIF-8 and reported a good agreement between simulation results and experimental IRM (infra-red microscopy) results. Guo et al (Guo et al, 2014) carried out GCMC simulations to study adsorption and separation of C 2 H 6 /CH 4 mixtures in IRMOF-1 and four different ZIFs . They showed that compared to MOR zeolite and IRMOF-1, ZIFs exhibit better C 2 H 6 separation performance for different mole fractions of C 2 H 6 /CH 4 mixtures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A probe radius of 1.86 Å (kinetic radius of the N 2 molecule) was employed for the calculations of surface area, and the COFs with zero S acc were eliminated so that the gas molecules studied in this work can adsorb into the remaining COFs. CH 4 /H 2 , CH 4 /N 2 , and C 2 H 6 /CH 4 mixtures were assumed to be equimolar as most of the experimental studies in the literature that we compared our results with consider equimolar mixtures. , Moreover, Guo et al , recently showed that composition does not significantly change the simulated C 2 H 6 /CH 4 and CH 4 /H 2 selectivities of ZIFs. To compute the mixture adsorption data in COFs, such as gas uptakes ( N ) and isosteric heat of adsorption ( Q st ), we performed GCMC simulations using the RASPA simulation code .…”
Section: Computational Detailsmentioning
confidence: 99%